Remote Sensing of Night-Time Light - Goldblatt, Ran (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Satellite measurements of night-time lights are widely recognized as a valuable indicator of human activity on Earth. These measurements capture the amount of light emitted from Earth at night and provide significant insights into a range of fields, including urbanization processes, socio-economic dynamics, local and regional GDP, economic impacts of conflicts, effects of epidemics on economic activity, and the various impacts of natural and man-made disasters. This reprint includes 16 articles that were published in the Remote Sensing Special Issue “Remote Sensing of Night-Time Light” and that highlight novel research on the remote sensing of night-time lights. The reprint aims to stimulate progress in the remote sensing research domain related to the utilization of night-time lights in a wide range of multidisciplinary and interdisciplinary domains, including urban studies, ecology, economics, oceanography, sociology, epidemiology, and more.